Causes of power quality problems (Power quality)
Introduces the different types of customer load and system events that can give rise to power quality disturbances. These disturbances include harmonic distortion caused by nonlinear loads, such as static power converters, magnetic core equipment, arcing loads, and thyristor-switched controllers. Looks also at power quality problems resulting from utility system events, such as faults, lightning, and switching operations. System resonance is also discussed as a cause of harmonic magnification.